The Idea of Progress in Science - marno marno marno (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
Scientific knowledge is knowledge that can be verified or based on facts through empirical research. Science exists because of proof, science exists because what we see is then empirically proven, giving birth to science. Science arises because contemporary thinkers want to build a framework for a new epistemological view and together agree to want to come out of the difficulties of ways of solving that are commonly put forward by modern thought. To achieve a belief in something, there must be at least 3 basic characteristics above. In turn, belief will produce habits in mind (habit of mind). Various beliefs can be distinguished by comparing habits in the thoughts produced. From there, we can distinguish between doubt and belief. From this doubt arises a kind of inquiry (investigation), through this investigation, finally which ushered in achieving human meaning (essential meaning) which is basically more important than Truth (truth), because meaning is the essence and substance of various phenomena of human life. Keywords: science, philosophy, belief, inquiry, meaing